Influencia del clima laboral y el proceso de selección en la rotación de personal en PwC Perú - Huaraz de la Haza, Valeria Mercedes (2023)
Given the concern about the high turnover of work, due to the growing rate of resignations from their jobs, this study aimed to identify the influence of the work environment and the selection process on staff turnover at PwC Peru, since 2019 to 2022. A correlational, retrospective, descriptive, relational, and applied research design was established, based on the hypothetical deductive method. There was the participation of 151 collaborators of the organization PwC-Peru, who, meeting the selection criteria, answered a structured questionnaire type Likert, of 21 items, previously validated by expert judges. The dimensions Organizational Communication, Workload and Recognition were measured to evaluate the Work Environment as an independent variable. The types of Recruitment and Selection Techniques were evaluated to assess the Selection Processes as a second independent variable and the Personnel Turnover criterion was established through its dimensions Satisfaction with compensation levels and Levels of organizational commitment. Pearson's correlation index of Staff Turnover was with Organizational Communication of 0.376, Workload of 0.487, Recognition of 0.691 and with the work climate of 0.686. Likewise, the Personnel Turnover statistic was with the Types of recruitment of 0.439, with the Selection Techniques of 0.599 and with the selection processes of 0.609. the combined relationship of Work Environment and Selection Processes with Staff Turnover was 0.721 (p<0.05). The alternative hypothesis "The work environment and the selection process influence staff turnover at PwC Peru" was accepted, given the significant relationship between the variables and their dimensions and the condition of dependency established between them.